Informal Savings Groups and Economic Empowerment of Women in Northern Division Kabale Municipality. - Atuheire, Tracy (Kabale University, 2024)
The study explored women’s informal savings groups and their impact on the economic empowerment of women in the Northern Division, Kabale Municipality. The objectives were to identify the women’s savings groups in the area, assess the contributions of informal savings groups to women’s economic empowerment, and examine the challenges these groups face in promoting women’s economic empowerment. A descriptive research design was employed, with data gathered through interviews and questionnaires. Regarding the women’s savings groups in the Northern Division, the majority of respondents identified self-help groups, while the least mentioned groups included livelihood groups and producer collectives. On the contributions of informal savings groups to women’s economic empowerment, the most cited benefit was access to financial savings tools, which provide a pool of capital for emergencies. Conversely, the least mentioned benefit was access to safe-keeping facilities like a secure box. Concerning the challenges faced by women’s informal savings groups, the predominant issue highlighted was the competition threatening the survival of individual groups, while the least reported challenge was the lack of capital or financial resources. The study recommended that the government should support women’s savings groups by offering loans to enhance their savings capacity, thereby increasing their income and improving the socio-economic welfare of their families.